GIQ - Revolutionizing Geospatial Ecosystem Development Through Public-Private Partnerships - S. Al Zeidi; P. Marpu; Y. Tarabalka; M. Balgi (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
The exponential growth of Earth observation (EO) data has created an urgent need for scalable, artificial intelligence (AI)-driven geospatial analytics platforms. Traditional GIS systems require specialized expertise, limiting their accessibility and usability for decision-makers. To address these challenges, the gIQ platform was developed as a Public-Private Partnership (PPP) initiative between the UAE Space Agency and Space42. gIQ integrates AI-powered geospatial analytics, cloud computing, and a marketplace for third-party applications, democratizing access to geospatial intelligence. This paper presents gIQ as a PPP success story, outlining its technical architecture, data acquisition pipeline, AI-driven insights, and business model. The platform leverages multi-source satellite data, AI-powered classification, real-time monitoring, and interactive visualization tools to deliver actionable geospatial intelligence. A marketplace model further enhances the ecosystem by enabling third-party developers to monetize AI models and geospatial services. The impact of gIQ extends beyond technological advancements. By bridging government, private sector, and research stakeholders, gIQ accelerates innovation in urban planning, environmental monitoring, and commercial space applications. The paper also discusses policy considerations, regulatory frameworks, and commercialization pathways that ensure the long-term sustainability of PPP-driven geospatial platforms (UAE Government, 2022). Finally, we outline future directions for expanding gIQ’s capabilities through cross-border PPPs and AI-powered decision support systems.